Deficiency of UBE3D in mice leads to severe embryonic abnormalities and disrupts the mRNA of Homeobox genes via CPSF3 - Yiwei Mi; Lu Yan; Yu Wu; Yufang Zheng (Cell Death Discovery)
Abstract Neurulation is a crucial event during vertebrate early embryogenesis, and abnormalities in this process can result in embryonic lethality or congenital disorders, such as neural tube defects. Through our previous phenotypic-driven screening in mice, we have identified UBE3D as a key factor for the neurulation process. By generating Ube3d knockout mice using CRISPR/Cas9 technology, we observed that homozygous mice exhibited severe growth retardation and malformation, ultimately dying between E10.5 to E11.5. In contrast to their wild-type and heterozygote littermates, homozygous embryos displayed small heads and unturned caudal neural tubes at E9.5. Our in situ hybridization and immunofluorescence experiments revealed high expression of UBE3D in the forebrain, neural tube, and heart at E9.5–10.5. Furthermore, RNA-seq analysis of the E10.5 embryos demonstrated that deficiency in UBE3D resulted in the downregulation of multiple Homeobox genes, including those specifically expressed in the forebrain and lumbosacral regions. We also discovered that UBE3D interacts with CPSF3, which is an endonuclease essential for the pre-mRNA 3’ end process. UBE3D could de-ubiquitinate CPSF3, and a deficiency of UBE3D leads to reduced levels of CPSF3 in both mouse and human cells. Overexpression of dominant negative mutants of CPSF3 was found to partially reduce mRNA levels of several Homeobox genes. In summary, our findings highlight that UBE3D is critical for early embryonic development in mice.